Respuesta a la aplicación de tres fertilizantes químicos y un abono orgánico en la producción de Jícama (smallanthus sonchifolius rob.) en la zona de Otavalo, provincia de Imbabura - Muenala Anrango, Jaime Roberto (2014)
The research was conducted in the canton Otavalo, Imbabura province, in order to study the application of three chemical fertilizers and organic production jicama (yacón Rob.). The treatments were chemical fertilizers; 10-30-10; 8-20-20; 18-46-00; bovinaza and absolute control without application. The design of randomized complete block (RCBD) with five treatments and three replicates were used for research. The variables were evaluated: days to emergence, plant height at 40; 80; 120 and 180 days after transplantation, diameter of the plant, days to harvest, weight of tubers, tuber number and yield in kg / ha. All variables applied were subjected to ANOVA using Tukey's test at 5%. The interpretation of the results it is concluded that the soil fertilization based on the annual requirement of N 80 - P 60 - K 80 kg / ha of 10-30-10; 18-46-00; 8-20-20 and compost bovinaza dose of 2000 kg / ha, obtained effectiveness in emergency, growth, development, tuber formation and yield in kg / ha crop of jicama.....